Superconductor-insulator transition in Josephson junction chains by quantum Monte Carlo calculations - Basko, D. M.; Pfeiffer, Frederik; Adamus, P.; Holzmann, M.; Hekking, F. W. J. (Physical Review B, 2020)
We study the zero-temperature phase diagram of a dissipationless and disorder-free Josephson junction chain. Namely, we determine the critical Josephson energy below which the chain becomes insulating as a function of the ratio of two capacitances: the capacitance of each Josephson junction and the capacitance between each superconducting island and the ground. We develop an imaginary-time path integral quantum Monte Carlo algorithm in the charge representation, which enables us to efficiently handle the electrostatic part of the chain Hamiltonian. We find that a large part of the phase diagram is determined by anharmonic corrections which are not captured by the standard Kosterlitz-Thouless renormalization group description of the transition.
CRIS-Team Scopus Importer:2023-03-08